Characterization of carbapenem-resistant gram-negative bacteria collected in the Sentinel Surveillance Program, 2018–2019. (July 2022) - Spicer, Lori; Campbell, Davina; Johnson, J. Kristie; Longo, Cynthia; Balbuena, Thomas; Ewing, Thomas; Karlsson, Maria; Rasheed, J. Kamile; Elkins, Christopher; Gargis, Amy; Lutgring, Joseph
Abstract : Background: Carbapenem resistance in gram-negative organisms is an important public health problem. The CDC conducted Sentinel surveillance in 2018–2019 to characterize these organisms from 9 facilities in 9 different states. Methods: Carbapenem-resistant Enterobacterales (CRE), Pseudomonas aeruginosa (CRPA), and Acinetobacter spp (CRA) obtained from clinical samples of patients in acute-care or long-term care facilities were submitted to the CDC. Identification was confirmed using matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF), and antimicrobial susceptibility testing (AST) was performed via broth microdilution for 27 antibiotics. All confirmed CRE and CRPA were tested for carbapenemase production (CP) using the modified carbapenem inactivation method (mCIM). The isolates that were mCIM-positive were assessed by real-time PCR for presence of bla KPC, blaN DM, bla VIM, and bla IMP. CP-CRE were also assessed for bla OXA-48-like. All confirmed CRA were tested for the same genes as CRPA and bla OXA-23–like, bla OXA-24/40-like, bla OXA-58–like, and bla OXA-235–like genes. Difficult-to-treat resistance (DTR) was defined as resistance to all β-lactams (excluding newer β-lactam combination agents) and quinolones tested. Results: The CDC confirmed 208 CRE, 161 CRPA, and 94 CRA. Table 1 summarizes AST results for a selection of drugs. We identified 112 (53.8%) mCIM-positive CRE and 6 (3.7%) mCIM-positive CRPA. The PCR results are summarized in Table 2 . One mCIM-positive and PCR-negative isolate was positive in a metallo-β-lactamase screen. Conclusions: Resistance among CRE and CRPA to newer β-lactam combination agents was detected. Options for treating CRA are limited. Of 112 CP-CRE, 85.7% harbored bla KPC; CP-CRPA were rare (3.7%); and most CRA harbored bla OXA-23-like (55.3%) or bla OXA-24/40-like (30.9%). Whole-genome sequencing is planned to better understand gene variants, sequence types, and additional resistance markers present among the isolates. Funding: None Disclosures: None